2005
DOI: 10.1074/jbc.m413614200
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Insulin and Transgenic Overexpression of UDP-glucose Pyrophosphorylase on UDP-glucose and Glycogen Accumulation in Skeletal Muscle Fibers

Abstract: UDP-glucose (UDP-Glc) and glycogen levels in skeletal muscle fibers of defined fiber type were measured using microanalytical methods. Infusing rats with insulin increased glycogen in both Type I and Type II fibers. Insulin was without effect on UDP-Glc in Type I fibers but decreased UDP-Glc by 35-40% in Type IIA/D and Type IIB fibers. The reduction in UDP-Glc suggested that UDP-Glc pyrophosphorylase (PPL) activity might limit glycogen synthesis in response to insulin. To explore this possibility, we generated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
1
11
1
Order By: Relevance
“…Importantly, high muscle glycogen content increased K m nearly twofold similar to alloxan-induced diabetes (20) and far above the physiological UDP-glucose concentration (28,30). Therefore, an increase in GS K m may have a limiting role for glycogen accumulation.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Importantly, high muscle glycogen content increased K m nearly twofold similar to alloxan-induced diabetes (20) and far above the physiological UDP-glucose concentration (28,30). Therefore, an increase in GS K m may have a limiting role for glycogen accumulation.…”
Section: Discussionmentioning
confidence: 92%
“…GS affinity for UDP-glucose is also regulated, but this regulation has received little attention despite the fact that the K m exceeds physiological concentrations (28,30). However, it has been reported that insulin increases GS affinity for UDP-glucose (33).…”
mentioning
confidence: 99%
“…The present study is novel in that it demonstrates that a more physiological mode of exercise (40 min of moderateintensity cycling) is able to reduce significantly the K m of GS for UDP-glucose in human subjects that are both insulin sensitive and insulin resistant (obese and type 2 diabetic). The GS K m of Ϸ0.2 mM UDP-glucose after exercise at a physiological concentration of G6P (0.17 mM) is far above the physiological concentration of UDP-glucose (0.03 mM) in resting muscles (28,31), and the increased affinity for UDPglucose would be expected to increase the rate of glycogen synthesis after exercise. Our data suggest that increased GS affinity for UDP-glucose represents an important physiological mechanism by which contraction promotes glycogen synthesis.…”
Section: Discussionmentioning
confidence: 94%
“…Expression for TPPP3 (tubulin polymerization-promoting protein family member 3), ATP1B1 (ATPase, Na+/K+ transporting, beta 1 polypeptide), BTG2 (BTG family, member 2), KDM2B (lysine-specific demethylase 2B), RGCC (regulator of cell cycle), KLF2 (Kruppel-like factor 2), VIMP (VCP-interacting membrane protein), CD93 (CD93 molecule), SORD (sorbitol dehydrogenase), LMCD1 (LIM and cysteine-rich domains 1), ITIH5 (inter-alpha-trypsin inhibitor heavy chain family, member 5), and CTNNA1 [catenin (cadherin-associated protein), alpha 1, 102 kDa] were increased in PeM compared to BPR, while expression of SLC7A2 [solute carrier family 7 (cationic amino acid transporter, y + system), member 2], ELL2 (elongation factor, RNA polymerase II, 2), NRIP1 (nuclear receptor interacting protein 1) and UGP2 (UDP-glucose pyrophosphorylase 2) were decreased by PRKAG3 in PeM. All of these downstream molecules of PRKAG3 are involved in either a) glucose metabolism (SORD [37], UGP2 [38], VIMP [39]), b) cytoskeletal formation (TPPP3 [40], CD93 [41], CTNNA1 [42]), c) cell cycle regulation (BTG2 [43], CD93 [41], RGCC [44]), d) transcription (ELL2 [45], KLF2 [46], LMCD1 [47]), e) transporters in cell/mitochondrial membranes (ATP1B1 [48], SLC7A2 [49]), f) hormone dependent nuclear receptor (NRIP1 [50]), g) ubiquitination (KDM2B [51], BTG2 [43]), or h) inflammatory response (VIMP [39]). The PRKAG3 associated interactions were derived from a list of DE genes identified by microarray assay that was performed with skeletal muscle tissues of PRKAG3 transgenic mice including missense point mutation and knock-out genotypes [52].…”
Section: Resultsmentioning
confidence: 99%